Genetic variability studies for yield and yield attributes in breeding lines of sesame (Sesamum indicum L.): GENETIC VARIABILITY STUDIES FOR YIELD AND YIELD ATTRIBUTES IN BREEDING LINES OF SESAME - P VAMSHI; K T RAMYA; M SANTHALAKSHMI PRASAD; J V RAMANA; S R KUMHAR (Journal of Oilseeds Research, 2021)
Twenty seven breeding lines along with three checks were evaluated for twelve different traits viz., days to 50% flowering, days to maturity, number of primary branches/plant, number of capsules/plant, capsule length, capsule width, plant height, harvest index, test weight, seed weight/capsule, oil content and seed yield/plot at ICAR-Indian Institute of Oilseeds Research, Hyderabad during late kharif, 2020. Analysis of variance (ANOVA) indicated significant variation among the genotypes for all the characters except for capsule width indicating the presence of substantial amount of variability for selection. High variation was observed for plant height, number of primary branches/plant, number of capsules/plant and seed yield/plot. The GCV for all the characters studied were lesser than the PCV indicating the influence of environment on expression of these traits. High heritability with high genetic advance was observed for plant height, number of primary branches/plant, number of capsules/plant, harvest index, oil content and seed yield/plot indicating additive gene action in the expression of these traits. Simple phenotypic selection may be effective for improving these characters. High heritabilitycoupled with low genetic advance was observed for oil content suggesting involvement of non-additive gene action in the expression of this trait indicating limited scope for further improvement through simple selection.